INTEGRATED FORMATION OF STUDENTS’ SOCIAL-CULTURAL COMPETENCE DURING FOREIGN LANGUAGE CLASSES IN INSTITUTIONS OF HIGHER EDUCATION - Rogulska, Oxana; Mahdiuk, Olha (Scientific Journal of Polonia University, 2023)
The article reveals the essence of the concept of ‘social-cultural competence’ and specifies its structural components. The peculiarities of the formation of students’ social-cultural competence during foreign language classes have been determined. The essence and expediency of the integrated formation of students’ social-cultural competence during foreign language classes in institutions of higher education has been revealed. The relevance of the study has been determined by the need for intercultural awareness of students for perfect and confident use of language in situations of intercultural communication. The purpose of the article is to reveal the expediency of the integrated formation of students’ social-cultural competence during foreign language classes in institutions of higher education.